2006
DOI: 10.1007/s00383-006-1812-7
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous aspiration versus open drainage of liver abscess in children

Abstract: Liver abscess, though a very grave problem, is rarely seen in infancy and childhood. Affected children are usually immunocompromised and are of poor socioeconomic status. Although liver abscess due to wandering ascarids is rare outside, it is common complication among children of Kashmir. Usual site of abscess is the right lobe of the liver and USG and CT of the abdomen are the main tools of diagnosis. The study was conducted over a period of 10 years from January 1991 to December 2000 and total of 129 cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
59
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 8 publications
6
59
1
1
Order By: Relevance
“…They concluded that open surgical drainage is the best modality of management for liver abscess. 5 We conclude with the message that although percutaneous drainage is safe and effective the open surgical and laparoscopic procedure are most reliable and effective means of management because we can deal not only with liver abscess, but also with associated intra-abdominal pathology.…”
Section: -12mentioning
confidence: 78%
See 2 more Smart Citations
“…They concluded that open surgical drainage is the best modality of management for liver abscess. 5 We conclude with the message that although percutaneous drainage is safe and effective the open surgical and laparoscopic procedure are most reliable and effective means of management because we can deal not only with liver abscess, but also with associated intra-abdominal pathology.…”
Section: -12mentioning
confidence: 78%
“…Although of considerable benefit, percutaneous drainage is not necessarily the best treatment for all patients and is associated with a significantly higher failure rate than surgical drainage. 5,[16][17][18] This is also evident from our series where 97 patients (60.63%) had USG guided aspiration and 31 patients (19.38%) had pigtail catheter drainage and were subjected to this mode of treatment, In Malik AA et al case study open surgical drainage was done in 127 cases, percutaneous drainage 26 cases and 16 cases were managed on iv antibiotics only with mortality in 19 patients, In Heneghan et al initially all patients were started with antibiotic therapy followed by USG guided percutaneous drainage in all patients out of which and only 2 patients required surgical intervention with no mortality. 3,4 Patients among them subsequently needed open surgical drainage because of inadequate response to percutaneous drainage.…”
Section: -12mentioning
confidence: 99%
See 1 more Smart Citation
“…Polymicrobial aetiology is common, and blood culture may be negative in about half of cases. 7,11 Eosinophilia, found in this case, may be due to previous helminthic infestation. Helminthiasis has been implicated in pyogenic liver abscess in children without pre-existing liver lesions, by inducing eosinophilia and granulomatous changes while passing through the liver.…”
Section: Discussionmentioning
confidence: 93%
“…1,2 Clinical features of liver abscesses in children include fever and right hypochondrial tenderness in about 100% of cases, hepatomegaly in 85%, and vomiting in 25%. 7 Symptoms such as cough, dyspnoea and severe chest pain suggest intrathoracic involvement due to sympathetic pleural effusion or pneumonia. Rarely, pyogenic liver abscess may present with thoracic empyema or pericardiac tamponade, due to rupture of an abscess in the left lobe of the liver.…”
Section: Introductionmentioning
confidence: 99%